(untitled) (Research, Society and Development, 2024)
Coffee is one of the most valuable commodities in the world, with a production chain that generates thousands of jobs and is fundamental to the economies of many countries. The production of coffee seedlings is a process to ensure crop success, aiming for a well-executed implementation, with quality seedlings. The objective of the present study is to evaluate the effects of shading levels with different shading colors on the production of Arabica coffee seedlings. The research was done in Poço Fundo City, Minas Gerais State (MG), Brazil, where the seedlings were grown under different shade colors (black, red, blue, and gray), having levels of 50% and 75%. Biometric parameters were evaluated, such as plant height, stem diameter, leaf area, dry and fresh mass, number of pairs of leaves, number of nodes, SPAD index and chlorophyll and carotenoid contents. The test carried out in the work was analysis of variance (ANOVA), followed by the Scott-Knott test to compare the means of the treatments. The results demonstrated that Arabica coffee seedlings grown under 75% Red Shade showed the best growth rates, emphasizing stem height and diameter, compared to seedlings grown under other shading conditions and in full sun. After 60 days, the seedlings under this condition still showed greater biomass and higher chlorophyll levels. On the other hand, plants exposed to full sun and 75% Black Shade showed lower growth and less biomass accumulation.